(untitled) (Third Sector Social Economic Review, 2017)
Co-operatives are structures that allow the fulfillment of the production and performance that are impossible to be fulfilled and overcome by an individual alone and require to be done collectively. For this reason, individuals come together and cooperate in informational, economic and technical fields. In places where small businesses are particularly widespread, business owners seek to meet their requirements at a lower cost by establishing cooperatives. Cooperatives are institutions that have an important place in today’s economic constructions, which are established by the partners investing capital. In developed countries, there are strong cooperative institutions in terms of economic size and areas of activity. Cooperatives operating in developing and underdeveloped countries appear as small organizations that are not comparable with developed country cooperatives in their economic sizes, technological facilities and effectiveness. There are also cooperatives operating in many different areas in our country. There is an insufficient cooperation and communication among them. If cooperative organizations open effective communication channels among themselves and establish a cooperation, they will be stronger and more effective; therefore they will be able to make a greater contribution both to their partners and the economy of the country.